Patient and graft survival after dual kidney transplantation with marginal donors in comparison to matched control groups - Yazdani, Babak; Marinez, Julian; Krüger, Bernd; Kälsch, Anna-Isabelle; Jung, Matthias; Chen, Gangyi; Leipe, Jan; Benck, Urs Tobias; Schnülle, Peter; Nuhn, Philipp; Keese, Michael; Schwenke, Kay; et al. (Transplantation proceedings, 2021)
Background - Postmortal organ donor rates remain low in Germany, whereas donor age has been increasing considerably in the last decades. As a consequence of low donation rates older and more marginal donor kidneys are accepted for transplantation. However, procured kidneys from very old a/o marginal donors may be considered as not suitable for transplantation as a single organ and subsequently be discarded. However, dual transplantation of both kidneys from such donors may provide an opportunity to nevertheless use these organs for renal transplantation, thereby providing the twofold nephron mass as a single kidney transplantation. - Methods - We compared in this retrospective analysis the outcome of 10 recipients of a dual kidney transplantation (DKT) with 40 matched recipients of a single kidney transplantation (SKT). Recipients were matched for donor and recipient age (ie, a maximum age difference of ±10 years in a ratio of 1:4 for DKT vs SKT recipients). In addition, a second SKT control group of 10 SKT recipients being transplanted immediately before each DKT recipient with a kidney from a donor aged ≥65 years was used for comparison. All renal transplant recipients were observed for up to 3 years or until July 31, 2020. - Results - Mean donor and recipient age was 77.2 ± 4.6/75.1 ± 6.6/82.1 ± 7.9 and 66.4 ± 5.8/66.1 ± 6.0/64.8 ± 8.4 for SKT group 1/SKT group 2/DKT, respectively. Procurement serum creatinine concentrations were significantly higher in the DKT group in comparison to the SKT control group 1 (P = .019) as was the rate of transplant artery atherosclerosis (P = .021). Furthermore, Kidney Donor Profile Index, and Kidney Donor Risk Index were significantly higher (P = .0138/P = .064, and P < .001/P = .038) in the DKT group than in SKT group 1 and 2. Rates of acute rejection and delayed graft function were not significantly different between groups, though biopsy-proven acute rejection was numerically higher in the SKT groups. Patient survival and overall and death-censored graft survival rates were also not significantly different between groups, although they tended to be higher after DKT. - Conclusions - DKT provides an opportunity to successfully use postmortal kidneys even from donors aged >80 years and a Kidney Donor Profile Index ≥95% for renal transplantation. DKT may thereby increase the available pool of donors to better serve patients with end-stage renal disease on the waiting list.
Gesehen am 18.01.2023